Collection and assessment of posterior airway secretions in horses: Review - Teixeira Borges Pereira, Matheus; Fernando Rocha de Oliveira, Paulo; Silva Martins , Thailan; Tatiele da Silva Rodrigues , Valquiria; Denian Silva dos Santos, Wendel; de Alencar Santos Júnior, Dinamérico (Pubvet, 2022)
Respiratory diseases have great impacts on equine health. Determining the diagnosis of inflammatory conditions of the lower (or posterior) respiratory system in horses depends on the association of history and clinical examination together with complementary exams, therefore, interventions performed by veterinary professionals must always be supported by good diagnostic methods so that the proper treatment is instituted. As complementary exams, the secretions of the lower airways can be submitted to cytology, bacterial culture, biochemical analysis, viral isolation and molecular tests. Among the collection methods, the use of transtracheal techniques stands out, including percutaneous transtracheal aspiration and lavage (LPP), percutaneous transtracheal aspiration (PTA) and endoscopic transtracheal aspiration (LTE). In addition to transtracheal techniques, bronchoalveolar lavage is possible, the latter being able to collect samples from the smaller and more distal airways. The present study aimed to gather the main information on the techniques of collection and evaluation of secretions from the lower airways in horses, which can serve as auxiliary material for diagnosis by veterinary professionals.
Keywords: Cytology; horses; transtracheal lavage; bronchoalveolar lavage